Degradação de cafeína por lacase de Trametes villosa - Torres, Bruno Henrique Czelusniak (2021)
Brazil is the largest coffee exporter in the world market and ranks second among the countries that consume the drink, corresponding to one-third of its coffee production, which places it as the world’s largest producer for over 150 years. Caffeine, the main methylxanthine found in coffee, is responsible for stimulating the central nervous system and for adverse effects such as reflux, increased blood pressure, osteoporosis, and muscle pain. Due to the adverse effects, there is an increase in the consumption of decaffeinated coffee, establishing the development of several methods to remove this compound. The conventional method used by most industries involves using solvents such as dichloromethane, which affects the product’s sensory characteristics and is harmful to the environment. The use of enzymes in the decaffeination process presents a viable alternative. It is a natural process in which enzymes with high activity, stability, and the possibility of recovery are used. In this context, laccase, an enzyme widely found in nature, produced via fungi, bacteria, and plants, catalyzes the oxidation or reduction of several compounds, such as caffeine. In this work, the extraction of caffeine in green coffee beans using water as an extracting solvent was evaluated. Based on the Box-Behnken statistical model, the process was evaluated with three variables, using the solute/solvent ratio, time, temperature, and as a response, the caffeine concentration in mg/g. Through the optimum point obtained in the extracts for caffeine (37.07 ± 1.94 mg/g), analyzes were performed on total phenolic compounds (36.72 ± 3.84 mg EAG/g) and total flavonoids (9.36 ± 0, 8 mg ECAT/g) before caffeine extraction. After optimization, the enzymatic degradation of caffeine was studied in which a factorial design with two independent variables was developed: mediator concentration (4-hydroxybenzoic acid) and pH. The laccase produced by the fungus Trametes villosa and the commercial laccase obtained 100% degradation yields under similar conditions. Raw laccase presented economic advantages due to the high cost of commercial laccase. However, a slight degradation process was observed. Through the degradation kinetics, it was possible to observe that the commercial laccase at pH 7.0 and 2 mM of HBA concentration can degrade caffeine in 30 minutes of reaction.